Gender pay gap a macro perspective. - Terada-Hagiwara, Akiko (Metro Manila, Philippines Asian Development Bank, 2018)
Gender wage inequality remains a persistent problem in both developing and developed countries. This paper explores this phenomenon using a unique data set that covers 53 economies spanning the period 1995 to 2010. Robust estimators show different factors influence the wage gap at different stages of development. Closing gender gaps in labor force participation an important factor in developing economies and education does little to equalize wages in developing economies. Higher-paying jobs should be created by expanding the service sector in these economies.
Keywords: Gender equality; Social rights -- Developing countries; Electronic books